Case Report: Cerebral Venous Sinus Thrombosis in a Young Child With SARS-CoV-2 Infection: The Italian Experience - Silvestri, Paola; Clemente, Anna; Spalice, Alberto; Febbo, Alessandra; Matera, Luigi; Accardo, Fabiana; Barbieri, Maria Antonietta; Villani, Alberto; Midulla, Fabio (Frontiers in Neurology, 2022)
Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in pediatric patients is usually characterized by fever, dry cough, and fatigue, or is asymptomatic and rarely presents with pneumonia. On the other hand, cerebral venous sinus thrombosis (CVST) could be a neurological sequela of the prothrombotic state triggered by coronavirus disease 2019 (COVID-19) both in adults and children. Case Report We present a case of a 15-year-old male child who was obese and had mild neurocognitive impairment. He was admitted to the pediatric emergency department and then diagnosed with CVST during SARS-CoV-2 infection. Conclusion During the COVID-19 pandemic, in patients presenting with neurological manifestations of CVST (headache, alteration of consciousness, focal deficit, or signs of endocranial hypertension), it is advisable to look for a current or recent infection of SARS-CoV-2, regardless of the presence of respiratory symptoms. In our patient, ongoing SARS-CoV-2 infection represents the only prothrombotic risk factor underlying the neurological disease.